The The Effectiveness Of Using Scrapbook Media To Improve Mufrodat Mastery Of Grade XI Of Al Hikmah Boarding School High School Batu - Abdul Muhith; Munirul Abidin, Munirul Abidin; Danial Hilmi, Danial Hilmi; Mochammad Indra Yumanto, Mochammad Indra Yumanto (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
This study aims to determine the effective of the influence using of scrapbook learning media on mufrodat mastery of eleventh grade students at Al Hikmah Boarding School High School Batu. This type of research is experimental research using a quantitative descriptive approach, as well as pre- and post-testing as data collection techniques. The population of this study is all students of Al Hikmah Boarding School Batu High School for the 2022-2023 school year. Data analysis techniques used to test hypotheses using SPSS 25.0-assisted multiple sample test formulas. Based on the results of pair 1 and pair 2 obtained sig. (2-tailed) from 0.000 < 0.05. Therefore, it can be concluded that there are differences in the average results of student mastery mufrodat for pre and post experimental classes and control classes. Then based on the results of the average score obtained from the pre- and post-test experimental categories, namely 48.27-71.54 in the experimental category and 51.54-58.85 in the control category. Therefore, it was concluded that Ha was accepted and Ho was rejected, which automatically shows that the using of scrapbook media in improving the mastery of the eleventh grade mufrodat of Al Hikmah Boarding School High School Batu is "effective".